The relationship and influence of mangrove density on density and diversity of macrobenthos in the mangrove ecosystems of Makassar City, Indonesia - Arfan, Amal; Ilyas, Muhammad; Sanusi, Wahidah; Rakib, Muhammad; Sukri, Irwansyah (Ecological Questions, 2025)
Mangrove ecosystems provide essential ecological services and support diverse benthic organisms, including macrobenthos, which serve as bioindicators of environmental stability. Understanding how mangrove structural attributes influence macrobenthic communities is crucial for effective coastal ecosystem management. This study aims to examine the relationship and influence of mangrove density on the density and diversity of macrobenthos in the mangrove ecosystems of Makassar City, Indonesia. Field data were collected across fifteen sampling stations representing different ecological settings. Mangrove density was measured using plot-based line transect methods, while macrobenthos were sampled using quadrat excavation and identified to the species level. Correlation and linear regression analyses were conducted to assess the statistical relationships between mangrove density and both macrobenthos density and diversity. The results revealed a strong, statistically significant positive correlation between mangrove density and macrobenthos density (r = 0.754, R2 = 0.569, p>0.05), indicating that denser mangrove stands tend to support more abundant benthic communities. In contrast, the relationship between mangrove density and macrobenthos diversity was weaker (r = 0.459, R2 = 0.2092, p>0.05), suggesting that diversity patterns are shaped by multiple environmental and ecological drivers beyond vegetation density alone. These findings highlight mangrove stand density as an important structural factor influencing macrobenthos density, while emphasizing the need to account for broader environmental variables when assessing diversity. Further research should integrate multivariate ecological parameters and long-term monitoring to guide effective conservation strategies.